2014
DOI: 10.1016/j.pragma.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Can pictures say no or not? Negation and denial in the visual mode

Abstract: In principle, verbal and image languages have different ways of coding conceptual content. Moreover, there is no reason to believe that both modes, the linguistic and the visual, can convey identical contents, and indeed, linguists have claimed that images are not suited for expressing the meaning of certain linguistic categories, like negation. As the linguistic literature argues convincingly, in natural language a distinction between negation and denial is justified. Employing insights in visual communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…However, some authors have defended recently an alternative account where negation does apply directly to images (Oversteegen & Schilperoord, 2014; see also Waskan, 2006). They presented images and observed that participants described them with a negation.…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors have defended recently an alternative account where negation does apply directly to images (Oversteegen & Schilperoord, 2014; see also Waskan, 2006). They presented images and observed that participants described them with a negation.…”
Section: Introductionmentioning
confidence: 99%
“…Ho discussed the performance of denial in the comment response genre--management responses to address negative online comments made by dissatisfied customers, and summarized that denial, whether used alone or in series, could aim at the asserted information, the rationality of customers, the responsibility of hotels and the seriousness of problems [1]. From the perspective of social semiotics, Oversteegen & Schilperoord (2014) explored some possibilities of visual negation and found that the essence of visual negation or denial was to some extent paradoxical to make it highly prominent by not displaying objects or attributes [11]. Bressem & Müller (2014) studied a set of gestures like sweeping away, holding away, throwing away and brushing away used by Germans in expressing negative acts such as denial [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is worth mentioning the researchers' attempt (Oversteegen, & Schilperoord, 2014) to identify images that imply negation. The authors argue that specific embodiments may convey negative content.…”
Section: Literature Reviewmentioning
confidence: 99%